CORRELATION BETWEEN SLEEP QUALITY AND INTERPRETATION OF THE COLD PRESSURE TEST IN STUDENTS OF THE FACULTY OF MEDICINE CLASS OF 2022 TADULAKO UNIVERSITY - Assar, Cindy Iriany Assar; Salikunna, Nur Asmar; Fitriah Handayani; Rahma Badaruddin (Universitas Tadulako, 2024)
Background: Sleep quality is one of the risk factors that influences the incidence of hypertension. Cold pressure test (CPT) is considered to have the potential that can be used as an evaluation in predicting the incidence of hypertension in the future. This study aims to determine the correlation between sleep quality and the interpretation of the CPT in medical faculty students class of 2022 at Tadulako University. Methods: This study uses a quasi-experimental, with one group pretest-posttest research design. In this sudy there is no control group. Samples were taken by total sampling technique with a total of 125 samples. The data collection method used the Pittsburgh Sleep Quality Index (PSQI) questionnaire to measure sleep quality and cold pressure test (CPT) to predict the risk of hypertension. Results: Based on the Spearman rank correlation test, the correlation coefficient is negative, which is -,007, which means the relationship between the two variables is not unidirectional, that means, the worse the sleep quality, the more hyperreactive the CPT interpretation. In this study, significance value correlation (p value) is 0,94. Conclusion: There is no significant relationship between sleep quality and cold pressure test (CPT) interpretation in medical students class of 2022 at Tadulako University.